ANALISIS IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA BANJIR ȍSTUDI PELAKSANAAN PERATURAN GUBERNUR NOMOR 39 TAHUN 2014 DI KELURAHAN PONDOK PINANG KECAMATAN KEBAYORAN LAMA KOTA ADMINISTRASI JAKARTA SELATANȎ - Dede Saidah (Jurnal Media Birokrasi, 2020)
Various policies have been implemented by the government and local government in disaster relief process through the utilization of resources with the support of the implementing agencies and public, but have not been able to achieve maximum results as expected. It reϔlected from lack of duties and functions government bureaucracy as policy implementers in performing ϔlood disaster relief. This study aims to describe how the implementation of ϔlood disaster relief policies held in the Administrative Village Pondok Pinang in District of Kebayoran Lama, South Jakarta. The method used in this research is descriptive qualitative approach, the technique of data collection is through interviews, observation and documents. This study focused on the implementation of ϔlood disaster relief policy. By using the Jones opinion factors include the organization, interpretation and application focus the determinants of policy and how the implementation of the policies implemented. SWOT analysis and Litmust Test used to analyze ϔlood disaster relief policy implementation. The results showed that the implementation of ϔlood disaster management policies in Pondok Pinang Village was not optimally implemented. Some of the obstacles encountered in policy implementation were due to the lack of capacity and commitment of the implementing apparatus as well as the lack of guidance and counseling carried out, which resulted in a lack of support and community participation in the success of the implemented policies. The results of the SWOT analysis are very strategic and strategic, namely 1) Maximizing the use of available personnel and budget resources in implementing ϔlood prevention policies in order to provide quality services to the community. 2) Increase public awareness to participate in the success of the policy through socialization, guidance and counseling. Keywords: Policy Implementation, Disaster Flood Relief